GQDs/W18O49/ tetragonal WO3 loaded on CN1-x to construct heterostructures for improving electrochemical performance. Issue 20 (15th October 2022) - Luo, Linhui; Du, Peng; Lei, Yun; Wang, Yongqin; Du, Beibei; Li, Can; Wu, Yuncui; Bao, Shenxu; Tu, Wenmao; Zou, Bingsuo
Abstract: In this study, the prepared GQDs/W18 O49 /WO3 (WCW) were loaded on g-C3 N4 with defects (CN1-x ) under the action of hydrothermal synthesis. The structure, morphology, optical properties, functional groups and surface group properties of the CN1-x @WCW composites were determined by XRD, TEM, UV–vis, FTIR and XPS tests. The electrochemical properties of the CN1-x @WCW composite were studied by i-t, EIS and M − S analysis. Compared with WCW, the instantaneous photoelectric efficiency, the photon current efficiency under the applied bias voltage, interfacial electron transfer and electron lifetime of CN1-x @WCW had been greatly improved. The results indicated that two-dimensional CN1-x with good conductivity could transfer electrons quickly, reduce the interfacial resistance and prolong the lifetime of electrons, thus inhibiting the recombination of photogenerated electron-hole pairs in WCW semiconductor. In addition, the possible mechanism was proposed and analyzed from the point of view of electron transmission.